Lynch syndrome–associated urothelial carcinoma: clinical and molecular findings from a single-institution cohort - A. Rametta; M. Barella; A. Scardino; F. Barbetta; E. Tamborini; F. Perrone; A. Busico; L. Agnelli; S. Rota; E. Gusmaroli; M. Stellato; A. Nuzzo; et al. (Familial Cancer, 2026)

Protistan assemblages in natural and man-made intermittent ponds of the New Jersey Pinelands - Micaela Kersey; Mihaela D. Enache; Nicholas A. Procopio; Patrick Burritt; Marina Potapova (Hydrobiologia, 2026)
Intermittent ponds of the New Jersey Pinelands are valuable ecosystems that support a diverse array of organisms including protists that play key roles in nutrient cycling and energy transfer within food webs. We used 18S-V9 DNA metabarcoding to explore protistan assemblages and their variation along a human-impact gradient in 30 natural and man-made Pinelands ponds. Heterotrophic protists were more diverse and abundant than phototrophs, especially in ponds surrounded by forest. Ciliates were the most abundant, while both ciliates and cercozoans were the most diverse taxonomic groups. Other prominent groups included amoebozoans, apicomplexans, peronosporomycetes, ochrophytes, dinoflagellates, and green algae. Protistan assemblage composition varied primarily with pH and along the land cover – eutrophication gradient. The most notable pattern in assemblage composition was a higher abundance of large-celled green algae in stormwater basins − man-made ponds with relatively low water quality, typically found in residential areas. While protistan assemblages in pond sediments were more diverse than those on submerged plants or artificial substrates, the latter still reflected the same environmental gradients as natural microhabitats.

Hereditary Spastic Paraplegia Associated with Ultra-Rare Variant Enrichment Encompassing the SYNE1, CAPN1 and PGAP1 Genes - E. Fratto; Maurizio Morelli; J. Buonocore; A. Quattrone; R. Procopio; M. Gagliardi; E. Tinelli; F. Fortunato; A. Gambardella (The Cerebellum, 2024)

Targeted education and outreach to neighbors of homes with high gross alpha radioactivity in domestic well water - Rebecca I. Schwartz; Jessie A. Gleason; Heidi S. O'Neill; Nicholas A. Procopio; Steven E. Spayd (Journal of Environmental Radioactivity, 2023)

Pre-assessments of plant conservation status in islands: the case of French Overseas Territories - S. Véron; A. Bernard; E. Lebreton; C. Rodrigues-Vaz; M. Durand; L. Procopio; M. Hélion; M. Gayot; G. Viscardi; G. A. Krupnick; C. M. S. Carrington; V. Boullet; et al. (Biodiversity and Conservation, 2023)

Occurrence and source identification of perfluoroalkyl acids (PFAAs) in the Metedeconk River Watershed, New Jersey - Nicholas A. Procopio; Robert Karl; Sandra M. Goodrow; Joseph Maggio; Judith B. Louis; Thomas B. Atherholt (Environmental Science and Pollution Research, 2017)

Development of Vegetation Models to Predict the Potential Effect of Groundwater Withdrawals on Forested Wetlands - Kim J. Laidig; Robert A. Zampella; Allison M. Brown; Nicholas A. Procopio (Wetlands, 2010)

Macroinvertebrate assemblages in blackwater streams draining forest land and active and abandoned cranberry bogs - Robert A. Zampella; John F. Bunnell; Nicholas A. Procopio; Dean E. Bryson (Wetlands, 2008)

Cyclooxygenase-independent induction of p21WAF-1/cip1, apoptosis and differentiation by L-745,337, a selective PGH synthase-2 inhibitor, and salicylate in HT-29 cells - G. Santini; M. G. Sciulli; R. Marinacci; O. Fusco; L. Spoletini; A. Pace; A. Ricciardulli; C. Natoli; A. Procopio; J. Maclouf; P. Patrignani (Apoptosis, 1999)